2003
DOI: 10.1176/appi.ajp.160.4.790
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Rates in Clinical Trials of SSRIs, Other Antidepressants, and Placebo: Analysis of FDA Reports

Abstract: These findings fail to support either an overall difference in suicide risk between antidepressant- and placebo-treated depressed subjects in controlled trials or a difference between SSRIs and either other types of antidepressants or placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
165
1
14

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(188 citation statements)
references
References 8 publications
8
165
1
14
Order By: Relevance
“…Although Khan et al 73 and Gunnell et al 74 concluded that there was not an impact on suicide secondary to the use of AD, there was an increase of self-aggressive behaviors. Some proposed mechanisms to explain the relationship among AD, ideas, and suicidal behaviors 75,76 , are psychomotor stimulation, depression paradoxical deterioration, akathisia, panic attack or anxiety onset, pharmacological switch to mania, induction to obsessive concern with suicide, and aggressive "borderline reactions" or paroxysmal disorders to electroencephalogram that might alter impulse control 61,[73][74][75][76] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although Khan et al 73 and Gunnell et al 74 concluded that there was not an impact on suicide secondary to the use of AD, there was an increase of self-aggressive behaviors. Some proposed mechanisms to explain the relationship among AD, ideas, and suicidal behaviors 75,76 , are psychomotor stimulation, depression paradoxical deterioration, akathisia, panic attack or anxiety onset, pharmacological switch to mania, induction to obsessive concern with suicide, and aggressive "borderline reactions" or paroxysmal disorders to electroencephalogram that might alter impulse control 61,[73][74][75][76] .…”
Section: Discussionmentioning
confidence: 98%
“…Some proposed mechanisms to explain the relationship among AD, ideas, and suicidal behaviors 75,76 , are psychomotor stimulation, depression paradoxical deterioration, akathisia, panic attack or anxiety onset, pharmacological switch to mania, induction to obsessive concern with suicide, and aggressive "borderline reactions" or paroxysmal disorders to electroencephalogram that might alter impulse control 61,[73][74][75][76] . For example, AD with short half-lives may induce, initially, serotonin level fluctuations, which may lead to akathisia, therefore increasing suicidal risk associated with desperation and unrest 77 .…”
Section: Discussionmentioning
confidence: 99%
“…In 1987, fluoxetine entered the market, but only in 2003 were SSRIs approved for use in children. In 2004, use of SSRIs increased and the idea that SSRIs might increase suicidal ideation was introduced in the public press [7][8][9]. Scharf commented that the issues around suicidal ideation were complicated by commercial influences and by the selection criteria used to recruit subjects for antidepressant trials.…”
Section: Can We Treat Adolescents With Ssris?mentioning
confidence: 99%
“…In an analysis of the FDA trials, in which patients typically received medication for shorter periods of time than in clinical practice, Kahn et al 26 found no difference between antidepressants (selective serotonin reuptake inhibitors or otherwise) and placebo in terms of suicide rates. Therefore, my sense is that the amount of time that patients take medications has a lot to do with their antisuicidal effects.…”
Section: -3mentioning
confidence: 99%